Copyright Protection of Graphic Design Works on Print on Demand - Ega Haidar Afif (UM Purwokerto Press, 2023)
Graphic design is a profession responsible for developing and designing specific visual communications through images that successfully convey important messages, express emotions and values. This is achieved through a harmonious combination of visual elements such as typography, color, proportion, etc. The importance of this profession lies mainly in consideration of the image of today's society. Images are starting to dominate text, which is why more and more communication, advertising and marketing strategies are emphasizing visual formats, whether through photographs, brochures or posters. From a business strategy point of view, graphic design is essential for strengthening a company's image and differentiating itself from the competition. In addition, you must master product design techniques in both print and digital forms. A graphic designer should thoroughly understand copyright protection, which is essential to avoid infringing on the creator's economic and moral rights. Copyright is the right to work in the fields of science, literature and art. Graphic design is one form of work that is protected by copyright. POD or Print On Demand, is a method where designers collaborate with suppliers to print their designs on white-labeled items whenever customers request them, such as blankets, mugs, or t-shirts. Graphic design is one type of creation that is protected by copyright under the Copyright Act. The existence of the Copyright Act has not made Indonesia compliant with copyright protection. There is still frequent use and procurement of graphic designs without obtaining permission from the creator, so it is necessary to study the rights of creators to graphic designs used in sales products in Indonesia.